Determination of cypermethrin in palm oil matrices - Zainudin, B.H.; Abu Bakar, N.K.; Muhamad, H. (2009)
In this study, a new method was developed for the determination of cypermethrin residue in both crude palm oil (CPO) and crude palm kernel oil (CPKO) using GC with electron capture detector. In this method, the oil was extracted with acetonitrile. Aliquots were cleaned-up using combined solid phase extraction (SPE), and a primary-secondary amine in combination with graphitized carbon black. The SPE cartridges were first conditioned and then eluted with acetonitrile. Cypermethrin recoveries from the fortified CPO samples were 87-98 with relative standard deviation (RSD) values of 4-8, while those for the fortified CPKO samples were 83-100 with RSD values of 3-10. Since good recoveries were obtained with RSD values below 10 in most cases, the proposed methodology will be useful for the analyses of palm oil samples. The method was successfully applied to the analysis of cypermethrin in real palm oil samples from various parts of Malaysia. No cypermethrin residue was found among 30 samples analyzed.